DECIPHER: Supporting the interpretation and sharing of rare disease phenotype‐linked variant data to advance diagnosis and research. Issue 6 (21st February 2022) - Foreman, Julia; Brent, Simon; Perrett, Daniel; Bevan, Andrew P.; Hunt, Sarah E.; Cunningham, Fiona; Hurles, Matthew E.; Firth, Helen V.
Abstract: DECIPHER (https://www.deciphergenomics.org ) is a free web platform for sharing anonymized phenotype‐linked variant data from rare disease patients. Its dynamic interpretation interfaces contextualize genomic and phenotypic data to enable more informed variant interpretation, incorporating international standards for variant classification. DECIPHER supports almost all types of germline and mosaic variation in the nuclear and mitochondrial genome: sequence variants, short tandem repeats, copy‐number variants, and large structural variants. Patient phenotypes are deposited using Human Phenotype Ontology (HPO) terms, supplemented by quantitative data, which is aggregated to derive gene‐specific phenotypic summaries. It hosts data from >250 projects from 40 countries, openly sharing >40, 000 patient records containing >51, 000 variants and >172, 000 phenotype terms. The rich phenotype‐linked variant data in DECIPHER drives rare disease research and diagnosis by enabling patient matching within DECIPHER and with other resources, and has been cited in >2, 600 publications. In this study, we describe the types of data deposited to DECIPHER, the variant interpretation tools, and patient matching interfaces which make DECIPHER an invaluable rare disease resource. Abstract : The DECIPHER web platform supports the sharing and interpretation of rare disease phenotype‐linked variant data to advance diagnosis and research.